Evaluation of P53 Expression in Ameloblastoma and Odontogenic Keratocyst by Immunuhistochemistry - Forooz Keshani; Seyed Amir Farzam; Mohammad Ali Seddigh; Atefe Esfandpour; Kosar Rafiei (مجله دانشکده دندانپزشکی اصفهان, 2023)
Odontogenic keratocyst (OKC), which is a developmental cyst has aggressive clinical behavior and its recurrence possibility is higher than other odontogenic cysts. The aim of this study was estimate biologic behavior of OKC with p53 immunohistochemistry comparison, as a tumor suppressor between OKC and ameloblastoma.Materials & Methods:In this experimental study, paraffin blocks of 14 OKC and 15 ameloblastoma, were collected from oral pathology department Qazvin University. After confirmation of H&E slides, they were stained immunohistochemically. Then the IHC slides were observed in terms of intensity and staining pattern. Finally, datawere analyzed with Wilcoxon and Man-Whitney test (p value <0.05).Results:In 86.7 % of ameloblastomawith positive expression p53 marker, 77% were weak expression and 33% were moderate expression. Among positive staining samples 84.6% were focally and 15.4% were scattered. In the case of OKC 11.4% indicated p53 marker that 80% showed weak expression and 20% showed moderate expression. 50% were focally and 50% were scattered. These findings support was not significially different between intensity and pattern of p53 marker between ameloblastoma and OKC (p value > 0.05).Conclusion:Expression of p53 was similar in ameloblastoma and OKC. Probably, high expression of p53 in odontogenic epithelial cells was one of the reasons for the OKC aggressive behavior. This findings vindicate biologic behavior of OKC.